GAYA KEPEMIMPINAN, IKLIM ORGANISASI, KOMPENSASI, DAN PERILAKU KERJA - Dedik Santoso (JIANA ( Jurnal Ilmu Administrasi Negara ), 2015)
Leadership Style, Organizational Climate, Employee Compensation and Work Behaviour. This study aims to know the influence of leadership style, organizational climate as well as compensation to the behavior of employees working at the Faculty of Social and Political Sciences, University of Riau either simultaneously or partially. The study population was the entire staff of the Faculty of Social and Political Sciences, University of Riau as many as 76 people. Data were collected using questionnaires. Data analysis method used is multiple linear regression method using SPSS for Windows version 17. The results showed that partially or jointly variable in this study both the style of leadership, organizational climate or compensation significantly influence the behavior of employees working at the Faculty of Social and Political Sciences, University of Riau. From the results of the study also found that organizational climate variables into the most dominant variable influencing the behavior of employees working at the Faculty of Social and Political Sciences, University of Riau followed by variable compensation for second dominant and leadership style.